Preparation of Discontinuous Cu/SiO2 Multilayers—AC Conduction and Determining the Measurement Uncertainty - Aleksandra Wilczyńska; Andrzej Kociubiński; Tomasz N. Kołtunowicz (Sensors, 2023)
This paper presents a test stand for testing alternating current electrical parameters of Cu–SiO2 multilayer nanocomposite structures obtained by the dual-source non-reactive magnetron sputtering method (resistance, capacitance, phase shift angle, and dielectric loss angle tangent δ). In order to confirm the dielectric nature of the test structure, measurements in the temperature range from room temperature to 373 K were carried out. The alternating current frequencies in which the measurements were made ranged from 4 Hz to 7.92 MHz. To improve the implementation of measurement processes, a program was written to control the impedance meter in the MATLAB environment. Structural studies by SEM were conducted to determine the effect of annealing on multilayer nanocomposite structures. Based on the static analysis of the 4-point method of measurements, the standard uncertainty of type A was determined, and taking into account the manufacturer’s recommendations regarding the technical specification, the measurement uncertainty of type B.